Gathering and Scattering Emily Dickinson’s Poetry - Antoine Cazé (Sillages Critiques)
The composition of Emily Dickinson’s poetic work has implied many stages of unbinding and rebinding her poems, from her own self-publishing practices (the now famous “fascicles”), through three editions of her Complete Poems (Johnson 1955, Franklin 1998, Miller 2016, all published by Harvard University Press) up to the recent uploading of her manuscripts as electronic archives on the Internet. It has fiercely divided scholars over what it has meant to “collect” Dickinson’s poems. This article presents certain aspects of this history, and contends that the combination of manuscript, print, and screen versions that we have today essentially corresponds to Dickinson’s writing project as a mixed media venture, always already predicated on re-mediation as a feature of collecting and dissemination. Ultimately, it examines Dickinson’s famous reticence to publish her poems in print as a component of a set of unconventional collecting practices.